Senam Yoga untuk Mengatasi Nyeri Punggung pada Ibu Hamil Trimester III di Puskesmas Duren Semarang - idris, Helma; Cahyaningrum; Anggit Anggraeni; Scolastika Cindy S.A (Universitas Ngudi Waluyo, 2023)
Around 46 – 58% of pregnant women experience low back pain which is found in the second trimester and 43.23% in the third trimester of pregnancy (Carvalo et al., 2017). In Indonesia 60% - 80% of back pain is experienced by pregnant women (Andriani, R.. 2019). Back pain is a symptom and not a disease. Back pain is mild discomfort to agonizing pain. Along with the enlargement of the uterus, the center of gravity in pregnant women will move towards the front. This transfer will cause the mother to have to adjust her standing position. Body changes like these can lead to lumbar curvature (lordosis) and thoracic compensatory spinal curvature (kyphosis). This kind of mechanism will occur in the fourth to ninth month of pregnancy, and will last up to 12 weeks after giving birth (Geta & Demang, 2020). Pain is a problem that is often encountered during pregnancy, especially when entering the second and third trimesters. The phenomenon of pain is a complex problem. The definition according to the International Society for The Study of Pain is